Projeto e construção de um scanner antropométrico baseado no método de triangulação a laser - Gazziro, Mario Alexandre (Universidade Federal de São Carlos, 2005)
Three-dimensional (3D) surface anthropometry enables us to extend the study to 3D geometry and morphology of human body. The purpose of this study is to build a whole 3D body scanner. Using lasers and cameras mounted on a scanning platform moved by a single motor and controlled by an embedded controller, a device has been implemented to capture the shape of the entire human body. One application case study (body fat percentage) is presented. The results suggests that the developed scanner can be useful for that particular case study and other like size surveying and medicine.
Keywords: Computação gráfica - hardware; Aquisição 3D; Antropometria; Instrumentação eletrônica; Processamento de imagens; Computer graphics; Scanner 3D; Image processing; Anthrometrics; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO